Living the Message: Embodied Da'wah and Religious Tourism Innovation at the Sunan Muria Pilgrimage Site - Susanto, Dedy; Musyafak, Najahan; Hakim, Lukmanul; Riyadi, Agus (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study investigates da’wah bil hal through religious tourism service innovations at the Sunan Muria Mosque and Tomb Foundation, addressing the limited scholarly attention to how practical service improvements can function as a medium for Islamic proselytization. Using a qualitative descriptive phenomenological approach, the research captures the lived experiences of pilgrims to explore how specific innovations shape their spiritual engagement, sense of comfort, and overall safety during visitation. Rather than merely listing developments, this study analyzes how architectural enhancements, spatial reorganizations, and management reforms collectively foster a conducive environment for da’wah by embodying Islamic values of hospitality, cleanliness, and communal care. The findings contribute to the broader discourse on religious tourism and Islamic communication by demonstrating that service-oriented innovations, when guided by spiritual intent, can reinforce religious identity and deepen pilgrims’ spiritual experiences. This research advances the understanding of da’wah bil hal as a contextual, experience-based form of Islamic outreach embedded in contemporary pilgrimage practices.